Entomogenous fungi from Andamans - ASHOK SHUKLA, M.M. ANSARI* and (Indian Phytopathology, 2002)
A number of surveys of entomogenous fungi in the Andaman Is., India, revealed the presence of 5 species. The pathogenicity of Metarhizium anisopliae to the Rhinoceros beetle [Oryctes rhinoceros], and of Beauveria bassiana, Paecilomyces fumosoroseus and Entomophthora sphaerosperma to unspecific hosts were confirmed in the laboratory.